2020 IEEE Symposium Series on Computational Intelligence (SSCI) 2020
DOI: 10.1109/ssci47803.2020.9308336
|View full text |Cite
|
Sign up to set email alerts
|

Automated Artifacts and Noise Removal from Optical Coherence Tomography Images Using Deep Learning Technique

Abstract: Optical Coherence Tomography (OCT) is a popular non-invasive clinical tool for the diagnosis of ocular diseases that provides micron-scale images of ocular pathology in vivo and in real-time. The cross-sectional OCT B-scan of Temporal-Superior-Nasal-Inferior-Temporal (TSNIT) peripapillary retinal profile is widely used to diagnose and monitor glaucoma. However, raw OCT images can be marred by noise and artifacts, especially vitreoretinal interface opacity: this can lead to segmentation error, misinterpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In recent years, research for symptomatic vitreous opacity image enhancement has made significant progress in several areas. These studies typically use traditional methods [11][12][13][14][15] and deep learning methods [16][17][18][19][20] to improve the quality and clarity of symptomatic vitreous opacity images. Some studies use traditional methods, such as filtering, to improve the quality of symptomatic vitreous opacity images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research for symptomatic vitreous opacity image enhancement has made significant progress in several areas. These studies typically use traditional methods [11][12][13][14][15] and deep learning methods [16][17][18][19][20] to improve the quality and clarity of symptomatic vitreous opacity images. Some studies use traditional methods, such as filtering, to improve the quality of symptomatic vitreous opacity images.…”
Section: Related Workmentioning
confidence: 99%
“…Although conventional methods perform well in some aspects, they may not be able to fully utilize the advantages of advanced techniques such as deep learning. In the case of deep learning methods [16][17][18][19][20], despite significant progress in image enhancement, a large amount of labeled data is usually required to train the model. Especially for symptomatic vitreous opacity image enhancement, obtaining a sufficient amount of labeling data can be a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Machine-based segmentation also often failed due to the presence of speckle noise, [20][21][22] low signal strength, 23 motion artifacts, 24 and vitreous opacity or vitreoretinal interface effects. [25][26][27] Furthermore, mis-segmentation occurs in eyes with advanced glaucoma or retinal pathology (e.g., diabetic retinopathy). 28 The benefit of using CNNs is their feature-agnostic ability, i.e., the ability to classify images by learning the position and scaling the variant structures within the data.…”
Section: (B))mentioning
confidence: 99%
“…Machine-based segmentation also often failed due to the presence of speckle noise, 20-22 low signal strength, 23 motion artifacts, 24 and vitreous opacity or vitreoretinal interface effects. 25-27 Furthermore, mis-segmentation occurs in eyes with advanced glaucoma or retinal pathology (e.g., diabetic retinopathy). 28…”
Section: Introductionmentioning
confidence: 99%
“…Nahida Akter et al proposed deep learning based method to remove noise from OCT images. The authors created and trained a U-Net model using OCT artifact-filled and artifactfree B-scans for investigation and shown that the U-Net performed better in terms of SSIM and PSNR values in removing the artefacts [11].…”
Section: Literature Reviewmentioning
confidence: 99%